Imaging Nigrostriatal Dopaminergic Deficit in Holmes Tremor with 18f-Pr04.Mz-Pet/Ct - Chana-Cuevas, P (Lippincott Williams and Wilkins, 2015)
Holmes tremor is an infrequent clinical syndrome characterized by unilateral rest, postural, and action tremor often secondary to a brain lesion. We herein report an interesting case of Holmes tremor studied with PETand 18F-PR04.MZ, a new high-affinity radioligand for dopamine transporters, currently under investigation at our center. 18F-PR04.MZ-PET can be useful to study the integrity of the nigrostriatal dopaminergic system to improve diagnosis and therapeutic outcome in patients with Holmes tremor and Parkinson disease. © Copyright 2015 Wolters Kluwer Health, Inc. All rights reserved.